SmartCounsel: Web-Based Application with TQM Framework to Enhance School Counseling Programs - Lakadjo, Mohamad Awal; Baid, Mohamad Fikri; Hasan, Moh Alwi; Muslim, Mohamad Riadi (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
This study aims to develop SmartCounsel, a web-based application that integrates Total Quality Management (TQM) principles to improve the quality of school counselling programmes. The research methodology used a comprehensive literature review to identify best practices and challenges in the implementation of TQM and educational technology. The study results show that SmartCounsel can overcome obstacles in counselling services with automation features for scheduling, monitoring and real-time feedback. The app supports hybrid counselling (online and face-to-face) and enables active engagement of students, teachers and parents, relevant to post-pandemic needs. The findings emphasise that implementing TQM in a digital platform not only improves service efficiency but also promotes continuous improvement. The study recommends further research to examine the impact of SmartCounsel on student learning outcomes and the effectiveness of counselling programs in various educational contexts.